2021
DOI: 10.2147/jmdh.s344729
|View full text |Cite
|
Sign up to set email alerts
|

A Gap Between Children’s Rights and Curricular Content in Health, Social Care, and Teacher Education Programs: An Exploratory Cross-Sectional Study

Abstract: Introduction Exposure to child maltreatment is a social and public health challenge that will require interprofessional collaboration to overcome. Evidence indicates that professional students in health, social care, and teacher education programs receive inadequate training in recognizing and responding to child maltreatment. The aims are to 1) assess the extent to which these students found that their uniprofessional education and a large-scale interprofessional learning (IPL) course had taught … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…These findings are in agreement with studies that have shown that teachers claim they lack competence and confidence and that they experience uncertainty about their role concerning pupils with experiences of domestic violence [17,18,76,77]. Teacher education study programs lack a curriculum developed for vulnerable children and children at risk [20,21,28,64,65,[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. Teachers are mandated to report child maltreatment, yet some teachers are reluctant to make such a report [93].…”
Section: Discussion Of Sensitive and Neutral Topicssupporting
confidence: 83%
See 2 more Smart Citations
“…These findings are in agreement with studies that have shown that teachers claim they lack competence and confidence and that they experience uncertainty about their role concerning pupils with experiences of domestic violence [17,18,76,77]. Teacher education study programs lack a curriculum developed for vulnerable children and children at risk [20,21,28,64,65,[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. Teachers are mandated to report child maltreatment, yet some teachers are reluctant to make such a report [93].…”
Section: Discussion Of Sensitive and Neutral Topicssupporting
confidence: 83%
“…The IPL initiative has previously been presented in detail [59][60][61][62][63][64][65][66][67]. In short, the IPL course is part of an educational intervention (Interprofessional Interaction with Children and Youth [INTERACT]) that aims to provide students with knowledge of and experience with interprofessional cooperation as well as interprofessional experience [59,68].…”
Section: The Ipl Coursementioning
confidence: 99%
See 1 more Smart Citation
“…As previously described, students in teacher education and child welfare programmes might be particularly interested in all topics involving children. 21 Self-selection bias cannot, therefore, be excluded, as respondents with strong opinions—in either direction—cannot be excluded (yet the diversity in our sample enhances the robustness of the findings). The anonymous data collection and inclusion of different educational backgrounds are the major strengths of this study, and to the best of our knowledge, no previous comparable study has been published.…”
Section: Limitations and Strengthsmentioning
confidence: 98%
“…In a quantitative follow-up study, we explored the extent to which the IPL first-year students learnt about the World Health Organisation's (WHO) core IPL competencies (roles and responsibilities, values and ethics, interprofessional communication and teams and teamwork). 21 , 17 While the majority learnt something about WHO competencies after the IPL course, the teacher and child welfare students achieved the best learning outcomes, including new knowledge about WHO competencies. 19 All the enrolled students were divided into pre-defined IPL groups each consisting of eight students representing health, social care and teacher education programs, aiming to facilitate that the students should learn with, from and about each other.…”
Section: Introductionmentioning
confidence: 99%